Synergistic antibacterial action of the iron complex and ampicillin against Staphylococcus aureus - Kosaristanova, Ludmila; Rihacek, Martin; Sucha, Frantiska; Milosavljevic, Vedran; Svec, Pavel; Dorazilova, Jana; Vojtova, Lucy; Antal, Peter; Kopel, Pavel; Patocka, Zdenek; Adam, Vojtech; Zurek, Ludek; et al. (BMC microbiology, 2023)
OBJECTIVES: Resistance to antibiotics among bacteria of clinical importance, including Staphylococcus aureus, is a serious problem worldwide and the search for alternatives is needed. Some metal complexes have antibacterial properties and when combined with antibiotics, they may increase bacterial sensitivity to antimicrobials. In this study, we synthesized the iron complex and tested it in combination with ampicillin (Fe16 + AMP) against S. aureus. METHODS: An iron complex (Fe16) was synthesized and characterized using spectroscopy methods. Confirmation of the synergistic effect between the iron complex (Fe16) and ampicillin (AMP) was performed using ζ-potential, infrared spectra and FICI index calculated from the minimum inhibitory concentration (MIC) from the checkerboard assay. Cytotoxic properties of combination Fe16 + AMP was evaluated on eukaryotic cell line. Impact of combination Fe16 + AMP on chosen genes of S. aureus were performed by Quantitative Real-Time PCR. RESULTS: The MIC of Fe16 + AMP was significantly lower than that of AMP and Fe16 alone. Furthermore, the infrared spectroscopy revealed the change in the ζ-potential of Fe16 + AMP. We demonstrated the ability of Fe16 + AMP to disrupt the bacterial membrane of S. aureus and that likely allowed for better absorption of AMP. In addition, the change in gene expression of bacterial efflux pumps at the sub-inhibitory concentration of AMP suggests an insufficient import of iron into the bacterial cell. At the same time, Fe16 + AMP did not have any cytotoxic effects on keratinocytes. CONCLUSIONS: Combined Fe16 + AMP therapy demonstrated significant synergistic and antimicrobial effects against S. aureus. This study supports the potential of combination therapy and further research.
Keywords: Methicillin-Resistant Staphylococcus aureus; Staphylococcal Infections; synergismus léků; Drug Synergism; Humans; Anti-Bacterial Agents; mikrobiální testy citlivosti; Antimicrobial activity; stafylokokové infekce; Microbial Sensitivity Tests; Ampicillin; Iron complex; Synergy; methicilin rezistentní Staphylococcus aureus; Staphylococcus aureus; lidé; antibakteriální látky; ampicilin